A Novel Targeted Microtubules Transformable Nanopeptide System Yields Strong Anti-Prostate Cancer Effects by Suppressing Nuclear Translocation of Androgen Receptors - Wang, Lu (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.